A crossflow model for an interacting capillary bundle: Development and application for waterflooding in tight oil reservoirs. (8th June 2017) - Li, Sheng; Dong, Mingzhe; Luo, Peng
Graphical abstract: Highlights: An new analytical solution was developed for a capillary bundle model. Cross-flows and flow rates were solved before and after water breakthrough. Narrow pore size distribution and high flow rate increase sweep efficiency. Low IFT greatly helps reach stable displacement front in tight oil reservoirs. Abstract: A new analytical method to calculate crossflow in an interacting capillary bundle has been proposed to analyze immiscible displacement processes in porous media. Capillary force, pressure equilibrium and mass balance were incorporated to develop algebraic equations for crossflow within the interacting bundle respectively before and after water breakthrough. By solving the equations analytically, flow rate in each capillary tube and crossflows among different tubes in the bundle were obtained as a function of water/oil interface positions at different times. The model was then applied to analyze the fluid dynamics of immiscible displacements. The whole process was modelled, from water first entering into the bundle to the moment that no more oil could be further produced. Eight water-displacing-oil cases, including specifically designed scenarios representing a tight reservoir, were modelled in an imbibition process to investigate the effects of pore size distribution, injection rate, and interfacial tension (IFT). The model successfully predicted fingering effect for a tight oil reservoir and even displacement front that could only be achieved by ultra-low IFT. The modelling results are highly consistent with previous experimental and simulation results in the literature. The theoretical model can be used to investigate the effects of different reservoir parameters in immiscible displacement process, such as permeability, wettability, and interfacial tension. The proposed interacting capillary bundle model leads to the pore network simulation in its simplicity as pore connection and topology information is not required.